DAMPAK POLITIK ETIS TERHADAP PERKEMBANGAN PENDIDIKAN DI INDONESIA - Manalu, Valentino; Pasaribu, Santha Sepatya Hotmaria; Butar-butar, Samuel; Sinaga, Rosmaida (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research discusses Dutch colonialism in the Indonesian education system. How does colonialism play a role in Indonesian education, especially ethical politics, influencing the education system in Indonesia Dutch colonialism in Indonesia lasted for more than three centuries, with an impact on various aspects of the life of the people of the Republic of Indonesia, one of which included the education system. Education is an effort made to change or develop attitudes, behavior, personal potential, intelligence in a better direction through the learning process. This research aims to determine the role of colonialism in the education system in Indonesia, starting with ethical politics. This research article uses a qualitative analysis method, specifically with literature analysis. According to (Safitri & Anggreani Dewi, 2021) This method is carried out by analyzing data from secondary sources of research articles related to the problems discussed in this research.